A Neural Model of Call-counting in Anurans - Houtman, David B. (Université d'Ottawa / University of Ottawa, 2012)
Temporal features in the vocalizations of animals and insects play an important role in a diverse range of species-specific activities such as mate selection, territoriality, and hunting. The neural mechanisms underlying the response to such stimuli remain largely unknown. Two species of anuran amphibian provide a starting point for the investigation of the neurological response to species-specific advertisement calls. Neurons in the anuran midbrain of Rana pipiens and Hyla regilla exhibit an atypical response when presented with a fixed number of advertisement calls. The general response to these calls is mostly inhibitory; only when the correct number of calls is presented at the correct repetition rate will this inhibition be overcome and the neurons reach a spiking threshold. In addition to rate-dependent call-counting, these neurons are sensitive to missed calls: a pause of sufficient duration—the equivalent of two missed calls—effectively resets a neuron to its initial condition. These neurons thus provide a model system for investigating the neural mechanisms underlying call-counting and interval specificity in audition. We present a minimal computational model in which competition between finely-tuned excitatory and inhibitory synaptic currents, combined with a small propagation delay between the two, broadly explains the three key features observed: rate dependence, call counting, and resetting. While limitations in the available data prevent the determination of a single set of parameters, a detailed analysis indicates that these parameters should fall within a certain range of values. Furthermore, while network effects are counter-indicated by the data, the model suggests that recruitment of neurons plays a necessary role in facilitating the excitatory response of counting neurons—although this hypothesis remains untested. Despite these limitations, the model sheds light on the mechanisms underlying the biophysics of counting, and thus provides insight into the neuroethology of amphibians in general.
Keywords: counting; anuran; frog; neural modeling; facilitated excitation